Trypsinogen activation peptide induces HMGB1 release from rat pancreatic acinar cells - Wang Guoliang; Liu Yan; Dui Danhua; Bai Liang; Liu Yao; Tian Fei; Wei Wei (Open Medicine, 2017)
The development of acute pancreatitis (AP) is associated with intracellular events in pancreatic cells, as well as with early and late inflammatory responses; however, their underlying mechanisms remain unclear. This study investigated trypsinogen activation peptide (TAP)-induced release of high mobility group box-l (HMGB1) from pancreatic acinar cells and how ethyl pyruvate (EP) affects this release.